INSTRUCTIONAL DESIGN IN TEACHING ENGLISH FOR LAW (A Project Based Learning Instruction in English II for Law Science Department) - Ummi Kultsum; Qosim Arsadani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2014)
Abstrak: Desan Intruksional Dalam Pengajaran Bahasa Inggris Hukum. Fakultas Syariah dan Hukum telah mulai mempersiapkan siswa mampu dalam menghadapi karir mereka sebagai ilmuwan hukum tidak hanya di nasional tetapi juga internasional. Kurikulum terpadu telah menjadi pilihan sebagai sistem pendidikan. Salah satu bentuk kurikulum terpadu adalah untuk mengkorelasikan antara atau di antara mata pelajaran. Untuk memenuhi hal ini, fakultas mencoba untuk mengembangkan Program ESP sebagai program pikiran dalam proses pembelajaran. Desain pembelajaran merupakan salah satu pendekatan yang dapat menjadi metode pilihan untuk dosen bahasa Inggris dalam memberikan subjek. English II diajarkan di kedua semester. Kata kunci: ESP Program, desain instruksional, Pengajaran Bahasa Inggris Hukum, Pembelajaran Berbasis Proyek (PBL). Abstract: Intructional Design In Teaching English For Law. Sharia and Law faculty has started to prepare its students able in facing their career as a law scientist not only in national but also international. Integrated curriculum has become a define choice as educational system aims for rigor and relevance. One of the forms of integrated curriculum is to correlate between or among subjects. To fulfill this, the faculty tries to develop ESP program as the mind program in learning process. Instructional design is one of the approaches that can be an option method for English lecturer in delivering the subject. English II is taught in the second of semester. This subject is being correlated under the notion of Project Based Learning (PBL).The design involves students totally to search, analyze, and conclude what they learn. This will make students doing what they learn, and then they will understand what they make. Keywords: ESP Program, Instructional design, Teaching English for Law, Project Based Learning (PBL)DOI:10.15408/sjsbs.v1i2.1544